Public Governance and leadership in times of Uncertainty. Intimacy of Politics and Science in Pandemic Management? - BC, Basheka (African Journal of Governance and Public Leadership (AJoGPL), 2022)
Societies of all times have withered the storms caused by social, political and economic disruptions. roughout the journey of mankind, problems have often presented themselves and solutions have always been found. Men and women who have always been in charge of the public arena have always attempted to get answers. Politicians and scientists have always intimately worked together. e current situation the world nds itself in orchestrated by the monstrous Covid-19 is not di erent. e question in the minds of the public is what has so far in uenced the containment measures of covid-19-politics or science? As the world quickly came to terms with the social, economic, political and technological e ects of covid-19, the politicians looked to scientists as the only hope. Of course, scientists equally looked to politicians for political guidance and facilitation. In many countries of the global, at the height of the second wave, political institutions failed and others crumbled but withstood the pressure. Public administrations demonstrated that they lagged 30 years behind the technological frontier.